Atypical Proliferative (Borderline) Serous Tumor in the Brain: A Case Report. (January 2018) - Xing, Deyin; Jenson, Erik G.; Zwick, Christopher A.; Rodriguez, Fausto J.; Kurman, Robert J.
Abstract : A 59-year-old woman with a remote history of invasive ductal carcinoma of the breast was found on a follow-up computed tomography scan of her brain to have a 1-cm lesion in the right frontal lobe in 2008. In the ensuing years, before her current admission, multiple imaging studies of the brain revealed that the lesion was stable and it was, therefore, interpreted as a small area of encephalomalacia related to a thrombosed cortical vein, a cavernoma, or treated metastatic breast cancer. In 2013, the patient underwent a bilateral salpingo-oophorectomy for ovarian tumors that were diagnosed as bilateral serous cystadenofibromas. A partial omentectomy showed no evidence of implants. In June 2016, the brain lesion was completely excised and diagnosed as an atypical proliferative (borderline) serous tumor. Immunohistochemical staining demonstrated that the tumor cells were immunoreactive for Pax8, WT-1, ER, and CK-7 and negative for Gata-3, PR, TTF-1, CDX-2, Napsin A, and CK-20, which was consistent with that diagnosis. We present a brief review of possible mechanisms to account for this unusual presentation and speculate that the most likely one is exfoliation of fallopian tube epithelial cells into the peritoneal cavity, which then gain access to lymphatics resulting in cells implanting in the brain and subsequently progressing to an atypical proliferative (borderline) serous tumor.